2017
DOI: 10.12691/jfnr-5-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Selected Traditional Foods Commonly Consumed in Saudi Arabia

Abstract: During the last few decades, Saudi Arabia experienced rapid nutritional transition associated with an alarming elevation in the prevalence of obesity and related chronic diseases. Traditional foods contribute to the usual diet of the population in Saudi Arabia and the nutritional evaluation of traditional foods is necessary to accurately estimate dietary intakes of the Saudi population. Therefore, the objective of the current work is to evaluate twentyfive traditional foods commonly consumed in Saudi Arabia ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
4
4
1
Order By: Relevance
“…The amount of total fatty acid in the foods consumed in Lebanon, Bahrain, Kuwait, Jordan and Saudi Arabia are extremely important given the elevated prevalence of non-communicable diseases in the countries (Table 3) 26 . Compared to our findings, increased fatty acid content was observed in Falafel that was also reported in many other Arab countries (14.3% in Saudi Arabia to 18.4% in Jordan) 23,24 .…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…The amount of total fatty acid in the foods consumed in Lebanon, Bahrain, Kuwait, Jordan and Saudi Arabia are extremely important given the elevated prevalence of non-communicable diseases in the countries (Table 3) 26 . Compared to our findings, increased fatty acid content was observed in Falafel that was also reported in many other Arab countries (14.3% in Saudi Arabia to 18.4% in Jordan) 23,24 .…”
Section: Resultssupporting
confidence: 58%
“…Furthermore, the Kuwaiti Baba Ghanouj's fatty acid content was moderately lower than that described in our study (8.7 and 9.4, respectively) 22 . Total fatty acid levels in Batata Mehchi ranged from 5.6% in Lebanon at 1970 to 5.9 % in Saudi Arabia 11,24 . Musiager et al, in 1998 21 , found double the amount of fatty acid levels in Bourgul bi banadoura, Chichbarak and yakhnet Bamia when compared to our study ( Table 3).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Hummus contains a relatively higher phytate content than cooked chickpeas [79]. However, this present study showed that iron bioavailability was significantly higher in hummus; it increased by more than 4-fold when both tahini and lemon juice were added to chickpeas (from 7.2 to 30.4 ng of ferritin/mg of total protein in Caco-2 cells, see Figure 3A).…”
Section: Hummus As a Promising Source Of Ironcontrasting
confidence: 51%